Measuring Intraspecific Variation in Flight-Related Morphology of Monarch Butterflies (Danaus plexippus): Which Sex Has the Best Flying Gear?. (26th October 2015) - Davis, Andrew K.; Holden, Michael T.
Abstract : Optimal flight in butterflies depends on structural features of the wings and body, including wing size, flight muscle size, and wing loading. Arguably, there is no butterfly for which flight is more important than the monarch ( Danaus plexippus ), which undergoes long-distance migrations in North America. We examined morphological features of monarchs that would explain the apparent higher migratory success and flight ability of females over males. We examined 47 male and 45 female monarch specimens from a project where monarchs were reared under uniform conditions. We weighed individual body parts, including the thorax (flight muscle) and wings, and computed wing loading and wing thickness for all specimens. When we compared each morphological trait between sexes, we found that females did not differ from males in terms of relative thorax (wing muscle) size. Females were generally smaller than males, but females had relatively thicker wings than males for their size, which suggests greater mechanical strength. Importantly, females had significantly lower wing loading than males (7% lower). This would translate to more efficient flight, which may explain their higher migratory success. Results of this work should be useful for interpreting flight behavior and/or migration success in this and other Lepidopteran species.